Bioorthogonal Noncanonical Amino Acid Tagging (BONCAT) Enables Time-Resolved Analysis of Protein Synthesis in Native Plant Tissue. Issue 3 (19th January 2017) - Glenn, Weslee S.; Stone, Shannon E.; Ho, Samuel H.; Sweredoski, Michael J.; Moradian, Annie; Hess, Sonja; Bailey-Serres, Julia; Tirrell, David A.
Abstract : Pulsing the noncanonical amino acid azidohomoalanine into Arabidopsis seedlings enables in-gel visualization, physical enrichment, and identification of newly synthesized proteins. Abstract: Proteomic plasticity undergirds stress responses in plants, and understanding such responses requires accurate measurement of the extent to which proteins levels are adjusted to counter external stimuli. Here, we adapt bioorthogonal noncanonical amino acid tagging (BONCAT ) to interrogate protein synthesis in vegetative Arabidopsis ( Arabidopsis thaliana ) seedlings. BONCAT relies on the translational incorporation of a noncanonical amino acid probe into cellular proteins. In this study, the probe is the Met surrogate azidohomoalanine (Aha ), which carries a reactive azide moiety in its amino acid side chain. The azide handle in Aha can be selectively conjugated to dyes and functionalized beads to enable visualization and enrichment of newly synthesized proteins. We show that BONCAT is sensitive enough to detect Arabidopsis proteins synthesized within a 30-min interval defined by an Aha pulse and that the method can be used to detect proteins made under conditions of light stress, osmotic shock, salt stress, heat stress, and recovery from heat stress. We further establish that BONCAT can be coupled to tandem liquid chromatography-mass spectrometry to identify and quantify proteins synthesized during heat stress and recovery from heat stress. Our results are consistent with a model in which, upon the onset of heat stress, translation is rapidly reprogrammed to enhance the synthesis of stress mitigators and is again altered during recovery. All experiments were carried out with commercially available reagents, highlighting the accessibility of the BONCAT method to researchers interested in stress responses as well as translational and posttranslational regulation in plants.